Cost Models in Digital Archiving: An overview of Life Cycle Management at the National Library of the Netherlands - Oltmans, Erik (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The number of institutions that are either considering the implementation of a digital archive or already started with an operational digital archive service is increasing. While technological and organisational challenges are well-studied and in few cases even well-defined, the subject of costs often remains untouched, which in many cases prevent organisations from new initiatives. In this paper two leading digital preservation techniques - migration and emulation - will be discussed in terms of life cycle management and associated cost models. Both techniques are studied and considered for implementation at the Koninklijke Bibliotheek, National Library of the Netherlands.